XRD, Mössbauer and magnetic properties of CdFe₂O₄, Zn₀₅(Co, Ni)₀₅Fe₂O₄ and Znx Mn₁₋xFe₂O₄ nanoferrites - Nhlapo, Toitoi Amos (University of the Free State (Qwaqwa Campus), 2012)
Abstract not available
Dissertation (M.Sc. (Physics))--University of the Free State (Qwaqwa Campus), 2012
Keywords: Ferrites (Magnetic materials) -- Synthesis; Mössbauer effect